Association between In-Laws Relationship and Domestic Violence Against Women (Journal of Social Sciences Review, 2025)
This study aims to investigate the impacts of in-laws' relationship with domestic violence against women followed by the quantitative analysis approach, based on a positivist paradigm usually based on a large sample size with statistical interpretation. The study was conducted in three villages of Union Council Darora such as Bar Cham, Koz Kas and Qala (Gandigar), District Upper Dir, Khyber Pakhtunkhwa Pakistan. The data were collected from 248 women above 25 years of age through questionnaires. The data were analyzed by descriptive and inferential statistics. The research found that domestic violence is often associated with in-law relationships. The resistance of women to their family obligations, lesser amount of dowry, restriction on women's movement and excessive social interaction are associated with domestic violence. Similarly, controlling women's autonomy by their mother-in-law, maintaining family honor, social stigma and more demands of women were the common reasons associated with domestic violence against women. Economic empowerment programs should aim to enhance women’s economic security, independence, and decision-making power. Social Support services, including counselling, legal aid, and shelter, should be strengthened and expanded to reach more survivors of domestic violence.
Keywords: Domestic Violence; Women; In-Laws Relationship; District Upper Dir; Economic Empowerment Programs